Challenges In Adapting ITIL (Information Technology Infrrtructue Library) Framework In Organizations - Phuspha, Sanniababoo (2011)
This paper basically analyzes the why factor fo the challenges to occur when implementing ITIL as part of continuous improvement efforts to a given problem. This paper will then propose a set of critical success factors for which the IT firms can use in ensuring the successful implementation of the ITIL models as a road map in solving the problems.